A review of the effects of using fermented agro-industrial by-products for nonruminants (Bangladesh Journal of Animal Science, 2024)
The world is going through its growing protein demand due to the increased human population. As a result, livestock production is getting accelerated to keep up with the pace with the increasing demand for animal protein. Furthermore, a good amount of animal protein comes from non-ruminants like poultry which mostly depend on cereals and concentrate-based feed as humans. The focus should be given to the agro-industrial by-products as alternative feed sources to reduce competition on human for food and make the low-quality feeds more efficiently digestible. This paper shows the effect of feeding fermented agro-industrial by-products on chicken, pig and fish. Feed quality changes, comparative procedures of fermentation, place of implementation and way forward are also discussed. In general, developing countries face problems with livestock feed scarcity. So, they are more conscious of removing this feed scarcity rather than having high-quality feeds. Therefore, fermentation is the technique best suited for agro-industrial by-products in countries where quality feeds are less available and unaffordable for budget farmers. This review depicts different fermentation to increase the nutrient contents of the agro-industrial by-products (rice bran, wheat bran, maize cob, maize straw, etc.). Additionally, this paper finds amelioration worldwide using this technique to increase nutrient digestibility, gut microbiota stabilization, immunization, and growth development with higher feed efficiency and overall raised performances of non-ruminant animals. In conclusion, this study tries to show the feed nutrient quality change and non-ruminants’ performance after fermentation is implemented. Also, it gives evidence about the possibilities of the effective execution of the fermentation procedure.Bangladesh Journal of Animal Science 53(4): 121-134, 2024